Effects of lactate consumption on blood bicarbonate levels and performance during high-intensity exercise - Morris, D. M.; Shafer, R. S.; Fairbrother, K. R.; Woodall, M. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
The authors sought to determine the effects of oral lactate consumption on blood bicarbonate (HCO3-) levels, pH levels, and performance during high-intensity exercise on a cycle ergometer. Subjects (N = 11) were trained male and female cyclists. Time to exhaustion (TTE) and total work were measured during high-intensity exercise bouts 80 min after the consumption of 120 mg/kg body mass of lactate (L), an equal volume of placebo (PL), or no treatment (NT). Blood HCO3- increased significantly after ingestion of lactate (p < .05) but was not affected in PL or NT (p > .05). No changes in pH were observed as a result of treatment. TTE and total work during the performance test increased significantly by 17% in L compared with PL and NT (p = .02). No significant differences in TTE and total work were seen between the PL and NT protocols (p = .85). The authors conclude that consuming 120 mg/kg body mass of lactate increases HCO3- levels and increases exercise performance during high-intensity cycling ergometry to exhaustion.